Rancangan Pembelajaran-Perkhidmatan : Satu Pembaharuan di Universiti Sains Malaysia - Ahmat, Sharom; Abdullah, Mohd Akhir (Penerbit Universiti Sains Malaysia, 1979)
Besides teaching and research, the service function of a University is becoming more and more important. This is primarily because the task of higher education is no longer the grooming of an elitist group. Indeed universities are being constantly challenged to meet the total development needs of the people. In this context, Malaysian university students have always been conscious of their service role. Unfortunately, well meaning as they may be, most of the service-oriented projects organized by the students suffer from the fact that they tend to be ad hoc efforts, often without thorough planning, and certainly lacking in continu-tv, review and assessment. Furthermore, most of these projects also do not make the best use of what students have to offer - their intelligence.